Similar effectiveness of dapagliflozin and GLP‐1 receptor agonists concerning combined endpoints in routine clinical practice: A multicentre retrospective study. Issue 8 (8th May 2019) - Fadini, Gian Paolo; Sciannameo, Veronica; Franzetti, Ivano; Bottigliengo, Daniele; D'Angelo, Paola; Vinci, Carmela; Berchialla, Paola; Arena, Salvatore; Buzzetti, Raffaella; Avogaro, Angelo
Abstract: Aims: According to cardiovascular outcome trials, some sodium‐glucose contransporter‐2 inhibitors (SGLT2i) and glucagon‐like peptide‐1 receptor agonists (GLP‐1RA) are recommended for secondary cardiovascular prevention in type 2 diabetes (T2D). In this real‐world study, we compared the simultaneous reductions in HbA1c, body weight and systolic blood pressure after initiation of dapagliflozin or GLP‐1RA as second or a more advanced line of therapy. Materials and methods: DARWIN‐T2D was a retrospective multi‐centre study conducted at diabetes specialist clinics in Italy that compared T2D patients who initiated dapagliflozin or GLP‐1RA (exenatide once weekly or liraglutide). Data were collected at baseline and at the first follow‐up visit after 3 to 12 months. The primary endpoint was the proportion of patients achieving a simultaneous reduction in HbA1c, body weight and systolic blood pressure. To reduce confounding, we used multivariable adjustment (MVA) or propensity score matching (PSM). Results: Totals of 473 patients initiating dapagliflozin and 336 patients initiating GLP‐1RA were included. The two groups differed in age, diabetes duration, HbA1c, weight and concomitant medications. The median follow‐up was 6 months in both groups. Using MVA or PSM, the primary endpoint was observed in 30% to 32% of patients, with no difference between groups. Simultaneous reduction of HbA1c, BP and SBP by specific threshold, as well as achievement of final goals, did not differ between groups. GLP‐1RA reduced HbA1c by 0.3% more than the reduction achieved with dapagliflozin. Conclusion: In routine specialist care, initiation of dapagliflozin can be as effective as initiation of a GLP‐1RA for attainment of combined risk factor goals.